Empowering Women through a User-Friendly Self-Help Group Website for Record Management - Kumar, Rohit (Journal of Advanced Research in Information Technology, Systems and Management, 2023)
The Women’s Self-Help Group (WSHG) for Record Maintaining is a platform designed to empower women by facilitating efficient record-keeping and loan management. In response to the evolving needs of these groups, we have developed a comprehensive website dedicated to the facilitation of WSHG activities, addressing the shortcomings of existing mobile applications and emphasizing inclusivity. This initiative aims to address the limitations of existing systems, providing a secure, user-friendly, and accessible solution for women engaged in self-help groups. The journey towards empowering women through technology is an ongoing one, and the commitment to continuous improvement, reflected in the future plans of language expansion, ensures that the benefits of this initiative reach an even wider audience. The proposed website ensures automation, security, and ease of use, overcoming challenges observed in current mobile applications.